2019
DOI: 10.1097/mpg.0000000000002459
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and Intravenous Lipid Titration During Routine Parenteral Nutrition in Small Preterm Infants

Abstract: Objectives: In case of hypertriglyceridemia (HiTG) during parenteral nutrition (PN), the 2018 European Society of Paediatric Gastroenterology, Hepatology and Nutrition guidelines recommend an intravenous (IV) lipid titration, but its consequences in small preterm infants are largely unknown. We compared macronutrient and energy intakes, growth, diseases associated with prematurity, and neurodevelopment in small preterm infants on PN who developed (cases) or did not develop HiTG (controls, CNTR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…More recently, in a retrospective study, Giretti et al [28] identified respiratory distress syndrome as a risk factor for HiTG in preterm newborns with BWs less than 1250 g. Despite the authors demonstrating an association between respiratory distress syndrome and lipid tolerance, the occurrence of respiratory distress syndrome preceded HiTG. In a similar population, the same research group, in a retrospective case-control study [29], did not find any relation between HiTG and BPD. Differently from our study, the authors did not correct the results for possible confounding variables.…”
Section: Discussionmentioning
confidence: 75%
“…More recently, in a retrospective study, Giretti et al [28] identified respiratory distress syndrome as a risk factor for HiTG in preterm newborns with BWs less than 1250 g. Despite the authors demonstrating an association between respiratory distress syndrome and lipid tolerance, the occurrence of respiratory distress syndrome preceded HiTG. In a similar population, the same research group, in a retrospective case-control study [29], did not find any relation between HiTG and BPD. Differently from our study, the authors did not correct the results for possible confounding variables.…”
Section: Discussionmentioning
confidence: 75%
“…They also recommend weekly monitoring of TG levels for infants on maintenance ILE. Whilst studies in very preterm infants found that growth, morbidities and neurodevelopment outcomes may not be affected by hypertriglyceridaemia (level > 2•8mmol/l) (37,38) , effects of TG levels or hypertriglyceridaemia on clinical outcomes in term and late preterm infants are unclear (3) .…”
Section: Discussionmentioning
confidence: 99%
“…The current meta-analysis of the effects of early high IVLE administration on episodes of hypertriglyceridemia favored the control groups. Correani et al reported that, with close monitoring of hypertriglyceridemia and IVLE titration at TG levels > 250 mg/dL, infants whose TG level measured >250 mg/dL during early postnatal period did not have growth, disease, and neurodevelopmental disadvantages, unlike the control group [ 32 ]. Therefore, high IVLE administration appears to be safe for preterm infants with regular TG monitoring and IVLE titration.…”
Section: Discussionmentioning
confidence: 99%